Efficacy of closed cell wet-suit at various depths and gas mixtures for thermoprotection during military training dives - Kelly, Karen R.; Palombo, Laura J.; Jensen, Andrew E.; Bernards, Jake R. (Frontiers in Physiology, 2023)
PURPOSE: To evaluate a closed-cell wet-suit for thermal protective capability during long duration cold water exposure at various depths. Additionally, to measure changes in skin and core temperature as a function of depth. METHODS: Thirteen (n=13) elite military divers and/or support divers who were tasked with cold-water training, participated in this study. To mimic various depths, the Ocean Simulation Facility (OSF) at the Navy Experimental Diving Unit (NEDU) was utilized across six diving days (one dive per day, for six total dives). Water temperature remained at 1.8-2.0˚C for all dives. The OSF was pressurized to simulate dive depths of 30, 50, and 75 fsw (2.27atm). Four divers dove each day and used the MK16 underwater breathing apparatus with gas mixes of either N202 (79:21) or HeO2 (88:12). Skin (chest, arm, thigh, calf) and core temperature (Tc), as well as hand and foot readings were obtained every 30 minutes during the 30 and 50fsw dives, and every 15 minutes during the 75fsw dive. The termination temperatures were previously determined to be 10˚C for hand and foot and Tc= 35˚C to prevent any non-freezing cold injuries. Mean skin temperature was later calculated using the Ramanathan (Ramanathan, 1964). RESULTS: Core temperature (TC) was significantly reduced across all dives (p=0.004); however, was preserved above the threshold for hypothermia (post dive Tc= 36.5±0.4). There was no effect of gas mix on TC. Mean skin temperature (TSK) significantly decreased (p<0.001) across all dives independent of depth and gas. Significant decrease in hand and foot temperatures resulted in the termination of three of the dives. There were no significant main effects for depth or gas, but there were significant main effects for time on hand temperature (p<0.001) and foot temperature (p<0.001). CONCLUSIONS: These findings demonstrate that core temperature is maintained above threshold for hypothermia. The changes in core and skin temperature are a function of dive duration independent of depth or gas for a closed-cell wet-suit in cold water at various depths. However, both hand and foot temperatures reached values at which dexterity is compromised.